The Translocation and Assembly Module (TAM) of Edwardsiella tarda Is Essential for Stress Resistance and Host Infection - Li, Mo-fei; Jia, Bei-bei; Sun, Yuan-yuan; Sun, Li (Frontiers in Microbiology, 2020)
Translocation and assembly module (TAM) is a protein channel known to mediate the secretion of virulence factors during pathogen infection. Edwardsiella tarda is a Gram-negative bacterium that is pathogenic to a wide range of farmed fish and other hosts including humans. In this study, we examined the function of the two components of the TAM, TamA and TamB, of E. tarda (named tamAEt and tamBEt, respectively). TamAEt was found to localize on the surface of E. tarda and be recognizable by TamAEt antibody. Compared to the wild type, the tamA and tamB knockouts, TX01ΔtamA and TX01ΔtamB, respectively, were significantly reduced in motility, flagella formation, invasion into host cells, intracellular replication, dissemination in host tissues, and inducing host mortality. The lost virulence capacities of TX01ΔtamA and TX01ΔtamB were restored by complementation with the tamAEt and tamBEt genes, respectively. Furthermore, TX01ΔtamA and TX01ΔtamB were significantly impaired in the ability to survive under low pH and oxidizing conditions, and were unable to maintain their internal pH balance and cellular structures in acidic environments, which led to increased susceptibility to lysozyme destruction. Taken together, these results indicate that TamAEt and TamBEt are essential for the virulence of E. tarda and required for E. tarda to survive under stress conditions.